# The elimination method for solving linear systems

Another way of solving a linear system is to use the elimination method. In the elimination method you either add or subtract the equations to get an equation in one variable.

When the coefficients of one variable are opposites you add the equations to eliminate a variable and when the coefficients of one variable are equal you subtract the equations to eliminate a variable.

**Example**

$$\left\{\begin{matrix} 3y+2x=6\\ 5y-2x=10 \end{matrix}\right$$

We can eliminate the x-variable by addition of the two equations.

$$3y+2x=6$$

$$\underline{+\: 5y-2x=10}$$

$$=8y\: \: \: \: \; \; \; \; =16$$

$$\begin{matrix} \: \: \: y\: \: \: \: \: \; \; \; \; \; =2 \end{matrix}$$

The value of y can now be substituted into either of the original equations to find the value of x

$$3y+2x=6$$

$$3\cdot {\color{green} 2}+2x=6$$

$$6+2x=6$$

$$x=0$$

The solution of the linear system is (0, 2).

To avoid errors make sure that all like terms and equal signs are in the same columns before beginning the elimination.

If you don't have equations where you can eliminate a variable by addition or subtraction you directly you can begin by multiplying one or both of the equations with a constant to obtain an equivalent linear system where you can eliminate one of the variables by addition or subtraction.

**Example**

$$\left\{\begin{matrix} 3x+y=9\\ 5x+4y=22 \end{matrix}\right$$

Begin by multiplying the first equation by -4 so that the coefficients of y are opposites

$${\color{green} {-4\}\cdot \left (3x+y\right )=9\cdot {\color{green} {-4}$$

$$5x+4y=22$$

$$-12x-4y=-36$$

$$\underline{+5x+4y=22 }$$

$$=-7x\: \: \: \: \: \: \: \: \: \: =-14$$

$$\begin{matrix} \: \:\; \:\: x\: \: \: \: \: \: \: \: \: \: \:=2 \end{matrix}$$

Substitute x in either of the original equations to get the value of y

$$3x+y=9$$

$$3\cdot {\color{green} 2}+y=9$$

$$6+y=9$$

$$y=3$$

The solution of the linear system is (2, 3)

**Video lesson**

Solve the linear system using the elimination method

$$\left\{\begin{matrix} 2y - 4x = 2 \\ y = -x + 4 \end{matrix}\right$$